Solubility and Dissolution Enhancement of Etoricoxib by Solid Dispersion Technique Using Sugar Carriers. (5th September 2011) - Das, Abhisekh; Nayak, Amit Kumar; Mohanty, Biswaranjan; Panda, Satyabrata
Abstract : The aim of the present study was to improve solubility and dissolution of the poorly aqueous soluble drug, etoricoxib by solvent evaporation technique using various sugar carriers, such as lactose, sucrose, and mannitol. Etoricoxib solid dispersions and their respective physical mixtures using lactose, sucrose, and mannitol were prepared in different ratios by solvent evaporation technique. The percent yield, drug content, saturation solubility, and in vitro dissolution of etoricoxib solid dispersions and physical mixtures were analyzed. Etoricoxib solid dispersions were characterized by FTIR spectroscopy, XRD, and DSC analysis. The FTIR spectroscopic analysis revealed the possibility of intermolecular hydrogen bonding in various solid dispersions. The XRD and DSC studies indicated the transformation of crystalline etoricoxib (in pure drug) to amorphous etoricoxib (in solid dispersions) by the solid dispersion technology. Both the aqueous solubility and dissolution of etoricoxib were observed in all etoricoxib solid dispersions as compared with pure etoricoxib and their physical mixtures. The in vitro dissolution studies exhibited improved dissolution in case of solid dispersion using lactose than the solid dispersions using both sucrose and mannitol. The in vitro dissolution of etoricoxib from these solid dispersions followed Hixson-Crowell model.